Jordanian green building approach for energy efficiency improvement - Alshorman, Abdullah; T. Talat, Nesrin; Alshorman, Malek; Alrawashdeh, Khalideh Al bkoor (International Journal of Engineering and Technology, 2018)
Energy saving, getting higher energy efficiency and reducing the negative impact on human health and environment can be achieved by green building (GB) approach. This concept includes considering the overall process of GB from design and construction to maintenance, which contributes to increase the efficiency of energy and economic. In this research an energy efficiency enhancement in the green buildings was investigated and results optimized based on the current proposed Jordanian green building model (JGBM). The total cooling and heating loads and saving energy were calculated for JGBM before and after amendments to the windows, walls, PV system, thermal insulation, and light type. The insulation (polystyrene) for external building walls has been adopted, also the double glazing instead of the current single glass. The electricity for the lighting consumption by LED and the potential of utilizing it in the building were analyzed. It has been found that implanting the JGBM considerations enables for real energy saving. In this study about 115 apartments and 73 houses were investigated in 4 Jordanian cities (Amman, Irbid, Zarqa, and Aqaba). Based on the analysis and model validation; suggested Jordanian green building model will save about 68% of the energy needed for cooling and 65% of the energy used for heating. The total saving of energy of Polystyrene insulation, PV system, double glazing windows, LED light and windows overhangs were 63.11%, 14.11%, 7.26%, 6.89% and 3.46% respectively.